O padrão de dispersão é sexo-assimétrico nos Euglossíneos (Hymenoptera: Apidae: Euglossini)? Um estudo de caso: Euglossa cordata - Cerântola, Natália de Campos Muradas (2009)
The Tribe Euglossini consists of relatively large bees, with metallic skin and bright color. Their extremely long tong enables them to use nectar resources that are inaccessible to other bees. Equipped with high capacity of dispersal, they are able to survive in disturbed environments, and compose even 25% of bees diversity in some forests. As important pollinators of many Angiosperms, especially Orchidaceae, they are fundamental to maintaining the stability of plant communities. Some species of the tribe are abundant in cities, in particular, Euglossa cordata. The genetic variability of five urban populations of this species was estimated by López-Uribe (2006) in adults caught while they were collecting nectar in flowers of Thevetia peruviana. The lack of structure found from nuclear loci (allozymes) and significant population structure for the 16S mitochondrial region are evidences that males and females showed different patterns of dispersion, where females are philopatrics while males are dispersers. To corroborate this hypothesis, this study aimed to determine the genetic structure of populations of E. cordata collected in flowers of T. peruviana in cities along a north/south transect of the State of São Paulo using mitochondrial and nuclear genetic data. The genetic differentiation found in the examined 12 populations was significant for the data sequence of mitochondrial cytb region (Fst=0.15; P<0.05), unlike observed for nine microsatellite loci (Fst=0.008; P>0.05). Allozymes loci were analyzed with the primary purpose of checking the individuals species; most polymorphisms showed that the populations are homogeneous, similar to the microsatellite data. Thus, our data from nuclear genes strongly suggest that there is no evidence of population structure in E. cordata, whereas mitochondrial data suggest structured population and that geographical proximity influence the events of colonization. Our results indicate that dispersal and colonization in E. cordata are characteristic attributes of males and females, respectively.